2014
DOI: 10.1016/j.devcel.2014.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA Modulates Alternative Splicing Regulators in Arabidopsis

Abstract: Alternative splicing (AS) of pre-mRNA represents a major mechanism underlying increased transcriptome and proteome complexity. Here, we show that the nuclear speckle RNA-binding protein (NSR) and the AS competitor long noncoding RNA (or ASCO-lncRNA) constitute an AS regulatory module. AtNSR-GFP translational fusions are expressed in primary and lateral root (LR) meristems. Double Atnsr mutants and ASCO overexpressors exhibit an altered ability to form LRs after auxin treatment. Interestingly, auxin induces a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
278
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 316 publications
(288 citation statements)
references
References 42 publications
8
278
1
1
Order By: Relevance
“…For example, this splicing variant may sequester or assemble splicing regulators and thereby affect the AS outcome of other pre-mRNAs, similar to what has been described for a long noncoding RNA in Arabidopsis. This long noncoding RNA can interact with nuclear speckle RNA-binding proteins and thereby alter the AS outcome of their target pre-mRNAs (Bardou et al, 2014). Further splicing of SR30.2 may also compete with nuclear decay of this splicing variant.…”
Section: Possible Alternative Routes For the Generation Of The Sr303mentioning
confidence: 99%
“…For example, this splicing variant may sequester or assemble splicing regulators and thereby affect the AS outcome of other pre-mRNAs, similar to what has been described for a long noncoding RNA in Arabidopsis. This long noncoding RNA can interact with nuclear speckle RNA-binding proteins and thereby alter the AS outcome of their target pre-mRNAs (Bardou et al, 2014). Further splicing of SR30.2 may also compete with nuclear decay of this splicing variant.…”
Section: Possible Alternative Routes For the Generation Of The Sr303mentioning
confidence: 99%
“…lncRNAs commonly function to regulate target RNA alternative splicing or affect chromatin topology and regulate neighboring gene transcription Bardou et al, 2014). In addition, lncRNAs could function as precursors of miRNAs and other small RNAs (Pant et al, 2008).…”
Section: Drir Regulates Aba-mediated Responses To Drought and Salt Stmentioning
confidence: 99%
“…The size of these RNA species is in hundreds of nucleotides range and show mRNA-like characteristics. Investigations for discovery of these regulatory components and their various functions are more focused in the model plant Arabidopsis (Bardou et al 2014) and food crop plants such as maize (Li et al 2014a), rice (Ding et al 2012) and wheat (Xin et al 2011). Recently, Wu et al (2012) with the help of NGS platforms identified long non-coding RNA associated with the secondary metabolism in the medicinal plant Digitalis purpurea.…”
Section: Discovery Of Small and Long Non-coding Rna Speciesmentioning
confidence: 99%